2016
DOI: 10.3109/02699206.2015.1115129
|View full text |Cite
|
Sign up to set email alerts
|

Entraining with another person’s speech rhythm: Evidence from healthy speakers and individuals with Parkinson’s disease

Abstract: This study examines entrainment of speech timing and rhythm with a model speaker in healthy persons and individuals with Parkinson's. We asked whether participants coordinate their speech initiation and rhythm with the model speaker, and whether the regularity of metrical structure of sentences influences this behaviour. Ten native German speakers with hypokinetic dysarthria following Parkinson's and 10 healthy controls heard a sentence ('prime') and subsequently read aloud another sentence ('target'). Speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…The current findings that the SPEAK OUT! group showed entrainment effects may relate to recent reports that individuals with PD are able to use metrical (temporal) auditory speech cues to entrain to speech [22]. Together, the data suggest possible strategies using entrainment in the auditory and visual channels as a possible means of addressing the speech difficulties of individuals with PD.…”
Section: Discussionsupporting
confidence: 65%
“…The current findings that the SPEAK OUT! group showed entrainment effects may relate to recent reports that individuals with PD are able to use metrical (temporal) auditory speech cues to entrain to speech [22]. Together, the data suggest possible strategies using entrainment in the auditory and visual channels as a possible means of addressing the speech difficulties of individuals with PD.…”
Section: Discussionsupporting
confidence: 65%
“…These disturbances have been described for syllable repetitions ( Skodda, Flasskamp et al, 2010 ; Skodda, Grönheit, & Schlegel, 2010 ), and connected speech ( Liss et al, 2009 ). In addition, Späth et al (2016) report that PwPD were less able to copy a rhythmical model during an entrainment task than healthy controls, and Grahn and Brett (2009) found that this speaker group was less able to process rhythmic tone sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In Parkinson's disease the ability to initiate speech (measured via turn-taking delay) and alignment of speech rhythm with stimuli is also disrupted. However, individuals with Parkinson's appear to perform better when metric rhythm is available from the stimuli, exploiting regular cues in speech (Späth et al, 2016). This underscores the role of the syllable-level envelope in temporal organization of both speech production and perception mechanisms.…”
Section: Box 1 Disruptions In Syllable Entrainment Results In Atypicalmentioning
confidence: 91%